Análisis de sensibilidad de la metodología exhaustiva desarrollada por el CIACUA para el diseño optimizado de redes de drenaje urbano (2017)
"In this thesis we want to perform a sensitivity analysis of the methodology proposed by Aguilar (2016), which makes a variation of the different parameters that are taken into account in the design. The change in hydraulic design and tracing of the study network should be observed by changing the cost function, pipe material, line segments defined for the linear approximation of the objective function and the filling ratio of the pipes. In this way, it will be possible to conclude that cost equation is more robust to changes in design parameters, and that a combination of these results in a greater minimization of construction costs. This is possible thanks to a statistical analysis and graph that will allow to compare each of the scenarios that are presented." -- Tomado del Formato de Documento de Grado.